Strategi Guru Dalam Menerapkan Pembelajaran Hots Menggunakan Model Problem Based Learning - Ummi Inayati (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
Education in Indonesia is currently undergoing a significant improvement. Particularly in welcoming the revolution era of the 4.0, which is required learning model with high level-thingking or commonly known as HOTS (Higher Order Thinking Skills). In addition to thinking critically and creatively, problem solving is also included as thinking characters in high-level skills. Solving problems in the learning process trains learners to resolve problems in real life. In fact, not all teachers can simply apply it. Therefore, HOTS learning using the problem based learning model requires strategy for more effective and efficient study. The research methods used in this study are qualitative descriptive, data collection techniques used by conducting observations, interviews in-depth and document research. The key informant in the study was a class III teacher at SDN Lengkong Bojonegoro, while the informant was a class III student. The data obtained is analyzed using interactive models (data collection, data presentation , reduction, drawing conclusions). The results of this study show that the teacher's strategy in implementing HOTS learning is a good problem based learning model. Visible from the indicators used through deep interview to the key informant and the informant. The obstacles experienced are differences in understanding, characteristics, learning style of students when learning, teachers are required to always be creative and innovative packing learning and the limitations of school facilities and infrastructure.